Effect of feeding lambs with a tanniferous shrub (rockrose) and a vegetable oil blend on fatty acid composition of meat lipids. (16th June 2016) - Francisco, A.; Alves, S. P.; Portugal, P. V.; Pires, V. M. R.; Dentinho, M. T.; Alfaia, C. M.; Jerónimo, E.; Prates, J. A. M.; Santos-Silva, J.; Bessa, R. J. B.
Abstract : The effects of feeding Cistus ladanifer (Cistus) and a blend of soybean and linseed oil (1 : 2 vol/vol) on fatty acid (FA) composition of lamb meat lipids and messenger RNA (mRNA) expression of desaturase enzymes was assessed. In total, 54 male lambs were randomly assigned to 18 pens and to nine diets, resulting from the combination of three inclusion levels of Cistus (50 v . 100 v . 200 g/kg of dry matter (DM)) and three inclusion levels of oil (0 v . 40 v . 80 g/kg of DM). The forage-to-concentrate ratio of the diets was 1 : 1. Longissimus muscle lipids were extracted, fractionated into neutral (NL) and polar lipid (PL) and FA methyl esters obtained and analyzed by GLC. The expression of genes encoding Δ5, Δ6 and Δ9 desaturases (fatty acid desaturase 1 ( FADS1 ), fatty acid desaturase 2 ( FADS2 ) and stearoyl CoA desaturase ( SCD )) was determined. Intramuscular fat, NL and PL contents were not affected by oil or Cistus. Oil supplementation reduced ( P <0.05) 16:0, c 9-16:1, 17:0, c 9-17:1 and c 9-18:1 FA and increased ( P <0.05) 18:2n-6, 18:3n-3 and the majority of biohydrogenation intermediates in NL. Cistus alone had few effects on FA of NL but interacted with oil ( P <0.05) by increasing t 10-18:1, t 10, t 12-18:2, t 10, c 12-18:2 and t 7, c 9-18:2. The t 10-/ t 11-18:1 ratio increased with both Cistus and oil levels. The c 9, t 11-18:2 did not increase ( P <0.05) with both oil and Cistus dietary inclusion. Oil reduced c 9-16:1, 17:0, c 9-17:1, c 9-18:1, 20:4 n -6, 22:4n-6 and 20:3n-9 proportions in PL, and increased 18:2n-6, 18:3n-3, 20:3n-3 and of most of the biohydrogenation intermediates. The Cistus had only minor effects on FA composition of PL. Cistus resulted in a reduction ( P <0.05) of 20:5n-3 and 22:6n-3 in the meat PL. The expression level of SCD mRNA increased ( P =0.015) with Cistus level, although a linear relationship with condensed tannins intake ( P =0.11) could not be established. FADS1 mRNA expressed levels increased linearly ( P =0.019) with condensed tannins intake. In summary, the inclusion of Cistus and oil in 1 : 1 forage-to-concentrate ratio diets resulted in a large increase in t 10-18:1 and no increase in c 9, t 11-18:2 or n-3 long chain poor in polyunsaturated fatty acids in lamb meat.